Paciente pediátrico con diabetes tipo 1 relacionado a una disminución visual progresiva. - Mera Robelli, Orlando Cristopher (2021)
Progressive vision loss is one of the most common complications in patients with diabetes mellitus, due to deterioration of the eye blood vessels. The retina, located at the back of the eye, is the one that recepts light and sends this signal through the optic nerve to the brain where it becomes the image we see. The diabetes present in infants corresponds to type 1 diabetes mellitus and is characterized by a condition at the level of beta cells in the pancreas, no longer producing one of the most important hormones, such as insulin. This type of disorder in children and adolescents was formerly known as "juvenile diabetes" or "insulin-dependent diabetes". The primary objective of this clinical case is to be able to assess the behavior of the paediatric patient with diabetes at a very young age and that manifests a progressive loss of vision derived from the pathology itself. When we study these types of cases, within the analyses that we perform and believe appropriate for the patient, are the tonemetry and an assessment with the slit lamp to be able to observe the structures of the eyeball and if necessary perform an ophthalmoscopy; During the review process we were able to show microangiopathies, which are thickening of small arteries that supply the retina, this visualized process are complications characteristic of diabetic retinopathy and would explain the progressive loss of vision in the patient. At the end of the study, I conclude by determining that the progressive loss of vision presented by the patient is due to the damage of small blood vessels that impair the function of the retina; in addition to bad habits such as being long periods of time in front of the computer and extensive reading hours. The refractive moons applied to the patient favorably changed their visual state and I did so by designing a corrective Lens by adding proper protections to the light. Before finishing, the patient was asked not to neglect the pharmacological treatment of the base disease, since if it is not controlled, the visual complications will be greater until it reaches blindness.